Effect of leaves on the rooting of cuttings of clove basil (Ocimum gratissimum L.) and anis (Ocimum selloi Benth.) - Purcino, Marivel; Machado, Marília Pereira; Biasi, Luiz Antonio (Revista de Ciências Agroveterinárias, 2012)
The aim of this work was to evaluate the effect of the presence of leaves on rooting of basil (O. gratissimum L.) and anis (O. selloi Benth.) cuttings. Ten-cm-long cuttings from the median region of branches were prepared through bevel cut in the base and right cut above the last axillary bud. The treatments consisted of cuttings with a pair of leaves, a pair of half leaves and non-leaves. Plastic trays containing commercial substrate were used in the planting. The cuttings were kept in a greenhouse under intermittent nebulisation and, at 45 days after planting, the following variables were evaluated: percentage of rooting, root number per cutting, mortality rate of the cuttings, the percentage of live cuttings without roots and percentage shoots. For both basil and anis for the best rooting results, it was found keeping a pair of leaves on the cuttings cut either in half or not. The absence of leaves drastically reduced the percentage of rooted cuttings of basil with high mortality of the cuttings (30%).